Investigating factors of the purchase intention of slaughterhouses for Halal Certification in Yogyakarta, Indonesia - Mohamad, Effendi; Muhammad Faishal; Asih, Hayati Mukti; Abdul Rahman, Azrul Azwan; Irawan, Fery; Adiyanto, Okka; Linarti, Utaminingsih (Malque Publishing, 2024)
The majority ofIndonesia's population adheres to Islam at 87.2%. The large number of adherents of Islam affects the number of requests for halal products, especially broiler meat in the Special Region of Yogyakarta. This is supported by the large number of Chicken Slaughter Houses (CSH) with a total of 1,232 in the Special Region of Yogyakarta. However, only 49 slaughterhouses have been certified halal by Majelis Ulama Indonesia(MUI). This is not proportional to the amount of CSH. The purpose of this study is to investigate the factors that influence the intention of CSH owners to make halal certificates using the Theory of Planned Behavior (TPB) model with the addition of religiosity and knowledge factors using purposive sampling method. The questionnaire was distributed face to face that targeted a minimum of 100 respondents with the specific criteria of CSH with age minimum 2 years old. The collected data was examined using the SPSS application, which is a multiple linear regression module. This study uses the variables religiosity, knowledge, perception control, subjective norms, attitudes, and intentions. The conceptual model consists of 2 models. The first model is the influence of religiosity factors, and knowledge of the attitude of CSH owners in making halal certification. The second model is attitudes, subjective norms, and perception control of CSH owners in making halal certification. The results showed that the knowledge and religiosity factors had a significant positive effect on the attitude of CSH owners in making halal certification. Attitude factors, perception control, and subjective norms have a significant effect on the intention of CSH owners in making halal certification. These factors can simultaneously explain the attitude of CSH owners in making halal certification by 2.9%, and the intention of CSH owners in making halal certification is 7.5% while the rest is influenced by other factors.